Coaching-Oriented Academic Supervision for Improving Elementary Teacher Performance of Aceh Tamiang Regency - Nasution, Rosnani; Yusrizal, Yusrizal; Munawar, Munawar (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Teacher performance is critical to improve learning quality in primary schools, but empirical research shows that many teachers continue to struggle with effective lesson planning, implementation, and assessment. This study investigates how coaching-based academic supervision provided by school leaders increases teacher performance via a reflective, dialogical, and collaborative developing process. Data were obtained using a qualitative descriptive technique, with in-depth interviews, observations, and documentation from principals, teachers, and supervisors at SD Negeri Paya Bedi and SD Negeri Pahlawan in Aceh Tamiang Regency. Data analysis included data reduction, data visualization, and conclusion drawing. The findings show that coaching supervision effectively assists teachers in (1) formulating clear, measurable, and contextual performance goals; (2) identifying strengths, weaknesses, and constraints in real instructional practices; (3) designing realistic instructional improvement strategies; and (4) developing strong commitment to implementing agreed-upon action plans through continuous monitoring. The coaching approach improves pedagogical and professional competencies by promoting teachers as active participants in professional development. This study shows that coaching-based academic supervision increases teacher ownership, reflective capacity, and motivation to sustainably enhance performance in elementary school settings.